Dorsal Dislocation of the Trapezoid with Metacarpal Instability: A Boxing Injury - Feder, Oren I.; Letzelter, Joseph P.; Hacquebord, Jacques H. (Journal of Wrist Surgery, 2020)
Background The second and third metacarpals are firmly attached, immobile structures which for the stable pillar of the hand. The trapezoid has been described as the keystone of the wrist, allowing a wide range of functional motion as well as inherent anatomic and biomechanical stability to the carpus.Case Description We describe a novel boxing injury with a 180-degree in situ dislocation of the right trapezoid with concomitant second and third carpometacarpal (CMC) joint dislocations. Open anatomic reduction of the trapezoid was obtained, and subsequent percutaneous pinning of the metacarpals allowed for a full functional recovery and return to sports at 6 months.Literature Review Combined trapezoid and CMC dislocations are extremely rare and have only been previously described in high-energy mechanism injuries, involving a direct dorsal force such as from the steering wheel in a motor vehicle collision. There are no previous reports of this injury occurring in the setting of direct axial load along the metacarpals in a clenched fist such as in a punch or fighting injury.Clinical Relevance The rare nature of this combined injury, its novel mechanism, and the difficulty in interpreting acute injury and postreduction radiographs require that the treating physician have a high degree of clinical suspicion for associated injuries when CMC dislocations are identified. Treatment strategies incorporating intraoperative fluoroscopy, open anatomic reduction of the trapezoid under direct visualization along with closed reduction, and pinning of the metacarpals reestablish carpal stability and provide excellent long-term results.
Keywords: carpal; instability; trapezoid